DC Fault Detection and Location in Meshed Multiterminal HVDC Systems Based on DC Reactor Voltage Change Rate - Li, Rui; Xu, Lie; Yao, Liangzhong (IEEE transactions on power delivery, 2017)
The change rate of the dc reactor voltage with predefined protection voltage thresholds is proposed to provide fast and accurate dc fault detection in a meshed multiterminal HVDC system. This is equivalent to the measurement of the second derivative of the dc current but has better robustness in terms of electromagnetic-interference noise immunization. In addition to fast dc fault detection, the proposed scheme can also accurately discriminate the faulty branch from the healthy ones in a meshed dc network by considering the voltage polarities and amplitudes of the two dc reactors connected to the same converter dc terminal. Fast fault detection leads to lower fault current stresses on dc circuit breakers and converter equipment. The proposed method requires no telecommunication, is independent of power-flow direction, and is robust to fault resistance variation. Simulation of a meshed three-terminal HVDC system demonstrates the effectiveness of the proposed dc fault detection scheme.